(3cJGH aj GdBOGHs
(3ChdgG (B:s
(3aUd cGf BOe eQGKkG hfhM fLGQkG hjfabhf Ydi GdCgd hGdYjGd ef GdWjH GdMdGd s
(3BNQgG (B:s
(3hJXgQ Ydi gPg GdCeI XdeI YXjeI hjchf XghQ GdOLGd hbJ XghQg ajgG hGddg CYde s
(3HgG GKQ WeSs
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW bOje LOkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdSjGSI hGdGLJeGYs